2015
DOI: 10.1177/1555412014567228
|View full text |Cite
|
Sign up to set email alerts
|

Stand by Your Man

Abstract: Although video gaming is becoming a more widespread activity beyond its historically core demographic of young males, participation in competitive gaming remains largely male dominated. Addressing this issue, this research examines the experience of female players in one of the world's most popular games, League of Legends. Two studies-one qualitative (with 15 participants) and the other quantitative (with 16,821 participants)-confirm that although female players accrue skill at the same rate as males, there r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 34 publications
0
47
0
2
Order By: Relevance
“…Results show that men prefer MMORPGs (Collins et al, 2012;Fuster et al, 2012;Li et al, 2013), sports games, and competitive online videogames, (Ratan, Taylor, Hogan, Kennedy, & Williams, 2015). Women tend to play for entertainment and to pass the time (Ko et al, 2005) and prefer videogames involving simulation, strategy games and mini-games.…”
Section: Discussionmentioning
confidence: 97%
“…Results show that men prefer MMORPGs (Collins et al, 2012;Fuster et al, 2012;Li et al, 2013), sports games, and competitive online videogames, (Ratan, Taylor, Hogan, Kennedy, & Williams, 2015). Women tend to play for entertainment and to pass the time (Ko et al, 2005) and prefer videogames involving simulation, strategy games and mini-games.…”
Section: Discussionmentioning
confidence: 97%
“…For all other games listed, female participation was even higher. The lowest estimate is provided by Ratan et al (2015) who found that only 4% of participants in their study on League of Legends were female (N = 18, 627).…”
Section: Genrementioning
confidence: 99%
“…To our knowledge, only two studies have assessed play time more directly, namely the works by and Ratan, Taylor, Hogan, Kennedy, and Williams (2015). In both cases, the authors assessed play time or number of game sessions using direct access to the game servers (Everquest 2 in the former case and League of Legends in the latter).…”
Section: Time-investmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Th e specifi c subject under consideration here is me, and my own qualitative fi eldwork; the specifi c domain I engage is intensive and competitive gaming, which remains heavily male-dominated (Harper, 2014;Ratan et al, 2015;Taylor, Jenson, & de Castell, 2009), even as the broader landscape of digital play has seen some recent tendencies toward greater inclusivity, however precarious (Chess, 2017;Shaw, 2015).…”
Section: Introductionmentioning
confidence: 99%